Analysis Difference between INR and D-dimer against Mortality COVID-19 patients - Herda Asyari, Claudia; Noor Chozin, Iin; Rakhma, Sastia (Riviera Publishing, 2023)
As of July 2022, COVID-19 has infected 565 million people, with 6.3 million deaths worldwide. The relationship between laboratory parameters with time to death and comorbidities has not been widely studied. This study determines the difference between INR and D-dimer on the mortality of COVID-19 patients at Dr. Hospitals. In a retrospective cohort study conducted in April 2020 - September 2021, 229 COVID-19 subjects were diagnosed with swab PCR. Data analysis included time to death from hospital admission divided into <7 days and >7 days, laboratory data, comorbidity data, and no comorbidity. Data were tested using Chi-Square for categorical data, Mann-Whitney, and Kruskall Wallis for numerical data. Overall, INR levels were significantly higher in subjects with comorbidities compared to those without (p<0.05). This was based on the time to death of subjects <7 days without comorbidities. In addition, the change from hypercoagulation to hyperfibrinolysis due to excessive coagulant consumption factors, resulting in increased PT and INR in severe COVID-19 conditions. Overall, it was found that INR levels were significantly higher in subjects with comorbidities compared to subjects without comorbidities, as well as D-dimer in subjects with a time of death >7 days without comorbidities was significantly higher compared to other subject groups.